A narrative study on competency biography of instructor of adult education: A case study of teaching artists in Korea - Yu-Lee Lee; Byung-Jun Yi (Adult Education Research Conference, 2014)
Dancing field has, from the beginning, expanded its category from expressing humans' internal desires with physical activities to being active in aesthetic areas. Today, the adult dancing education is the medium where emotional, physical, and psychological abilities can be expressed. The fact that people utilize dance as a learning method, shows their acknowledgement of the value of dance as an educational method. It can be said that dancing leads people to evolve and grow ideologically. Thus, dance education not only simply teaches producing or mimicking an art piece, but also helps to develop an individual into a creative person through self-cultivation and development of one's social skills.